Konsep Friendship Perspektif Wahbah Az-Zuhaili dalam Tafsir Al-Munir - Annisa Solihah Nurjannah; Arif Firdausi Nur Romadlon; Edy Wirastho (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
This study explores the concept of friendship from the perspective of Wahbah Az-Zuhaili as presented in Tafsir al-Munīr. According to Az-Zuhaili, friendship is not merely a social relationship but a bond that carries spiritual, moral, and religious responsibilities. Based on his interpretation of several Qur’anic verses, including Surah Az-Zukhruf [43]:67, Al-Furqan [25]:28–29, Al-‘Ashr [103]:3, and Al-Hujurat [49]:10, he asserts that true friendship is grounded in faith, piety, and love for Allah (al-ḥubb fī Allāh), and thus yields benefits both in this world and the hereafter. Conversely, friendships based on worldly interests or values that contradict divine guidance lead only to regret and enmity on the Day of Judgment. Az-Zuhaili emphasizes the crucial role of selectivity in choosing companions as a means to preserve and strengthen one’s faith and moral character. Furthermore, he highlights the social function of friendship in Islam as a medium for mutual counsel in truth and patience, and as a force that reinforces Islamic brotherhood (ukhuwah Islamiyah). Accordingly, Az-Zuhaili’s concept of friendship integrates both vertical (ḥablun minallāh) and horizontal (ḥablun minannās) dimensions, making it a vital component in the construction of a balanced, caring, and hereafter-oriented Islamic society.